1994
DOI: 10.1080/01496399408002189
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Gallium (III) from Basic Sodium Aluminate Solution by Alkanoyl Oxines

Abstract: Alkanoyl oxines have been used for the extraction of gallium from basic solution, especially for the selective recovery of gallium in the presence of excess aluminum from Bayer process sodium aluminate liquor. 5-Alkanoyl-8-hydroxyquinolines (R.CO.Ox), where R is the alkyl group C13H27 (myristoyl), C I~H~~ (palmitoyl), and C17H35 (stearoyl) were synthesized by the Fries rearrangement from the corresponding acid chloride and sodium oxinate using AlC13 as catalyst. The synthesized alkanoyl oxines were capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Liquid-liquid extraction [2][3][4][5] is effective for separation and preconcentration of cations, including these metals. Several researchers have studied the fundamental extraction behavior [6][7][8][9][10][11][12][13][14] and the mutual extractive separation [15][16][17][18][19][20] of trivalent group 13 metal cations using many kinds of extractants. [21][22][23][24][25][26][27][28] In spite of its versatility, multi-stage extraction procedures, disposal of large volumes of organic wastes and expensive treatment are the main problems.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Liquid-liquid extraction [2][3][4][5] is effective for separation and preconcentration of cations, including these metals. Several researchers have studied the fundamental extraction behavior [6][7][8][9][10][11][12][13][14] and the mutual extractive separation [15][16][17][18][19][20] of trivalent group 13 metal cations using many kinds of extractants. [21][22][23][24][25][26][27][28] In spite of its versatility, multi-stage extraction procedures, disposal of large volumes of organic wastes and expensive treatment are the main problems.…”
Section: Introductionmentioning
confidence: 99%
“…), C15H31 (P.Ox), and C17H35 @.Ox)] have been synthesized by a modified route based on the Fries rearrangement (4), and their structures were confirmed by elemental analysis and IR spectroscopy (5). Although this study showed that Ga could be selectively extracted by a CHC13 solution of these reagents from a basic solution of pH 13 containing up to 20-fold of aluminum, the extraction was rather slow, requiring a time period of 60 minutes at 40°C.…”
Section: Co-r O Hmentioning
confidence: 99%
“…The reagents were of analytical grade purity unless otherwise stated. 5-Alkanoyl-8-hydroxyquinolines, i.e., myristoyl oxine (M.Ox), palmitoy1 oxine (P.Ox), and stearoyl oxine @.Ox), were synthesized in the department laboratories as described previously (4,5).…”
Section: Reagents and Solutionsmentioning
confidence: 99%
“…At the same time, oxine and oxine-type chelating group bearing resins are selective toward Cr(III) ions and do not retain Cr(VI) ions [7,8]. In previous studies, 5-palmitoyl-8-hydroxyquinoline (POx) [14,15] functionalized Amberlite XAD-2 chelating resin column was used to separate Ga from Al in strongly the alkaline aluminate liquor from the Bayer process for alumina manufacture [16], and for the speciation analysis of Ga(III) [17]. Immobilization of the ligand (palmitoyl oxine) on the resin was achieved by chloromethylation of the XAD-copolymer followed by Friedel-Crafts alkylation of the oxine derivative with this chloromethylated intermediate [16,17].…”
Section: Introductionmentioning
confidence: 99%